Comparison of the effects of ticagrelor and clopidogrel on heart rate variability and heart rate turbulence in patients with percutaneous coronary interventions - Yagcioglu, Pinar (J Saudi Heart Assoc, 2020)
INTRODUCTION: Clopidogrel and ticagrelor are commonly used, antiplatelet agents. Ticagrelor has an effect of enhancing the plasma level of adenosine that may alter the autonomic function. The aim of this study is to compare the effects of ticagrelor and clopidogrel on heart rate variability (HRV) and heart rate turbulence (HRT). METHODS: Thirty subjects who performed percutaneous coronary intervention (PCI) were included in the randomized, crossover study. These patients were divided into two groups. Clopidogrel or ticagrelor was administered in two different testing sessions (1-month treatment for each session). In group 1, clopidogrel and ticagrelor treatment were used while in group 2, ticagrelor and clopidogrel treatment were used respectively. Three times rhythm Holter recording (baseline, 1st and 2nd month) was performed. The HRV (time domain and frequency domain) and HRT (turbulence onset (TO) and turbulence slope (TS)) parameters were analyzed from the Holter recordings. RESULTS: According to baseline Holter recording, pNN50 (5.82 ± 5.83 vs 10.56 ± 8.28; p = 0.03) and HF(nu) (6.85 ± 9.33 vs 9.53 ± 7.41; p = 0.04) parameters were higher in group 2 than in group 1, while TO(0.004 ± 0.02 vs −0.01 ± 0.02; p = 0.01) parameter was positive and higher in group 1 than in group 2. In the second month, the LF/HF ratio (4.47 ± 2.43 vs 3.18 ± 2.45; p = 0.04) was higher in group 1 than in group 2. However, when the evaluation was done within the groups themselves, there were no statistically significant differences in HRV and HRT parameters obtained before and after clopidogrel and ticagrelor administration in group 1 and group 2. CONCLUSION: Ticagrelor and clopidogrel treatments did not have a significant effect on HRV and HRT parameters.